How Large is the Endowment Effect in the Risky Investment Game? - Stein T. Holden; Mesfin Tilahun (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2021)
The risky investment game of Gneezy and Potters (1997) has been a popular tool used to estimate risk tolerance and myopic loss aversion. Holden and Tilahun (2021) tested and found that the simple one-shot version of this game that is attractive as a simple tool to elicit risk tolerance among respondents with limited education, produce significant endowment effects in two variants of the game where alternatively safe and risky initial monetary endowments are allocated. In this paper, we use an alternative treatment that does not induce endowment effects. This allows us to establish a benchmark to assess the relative size of the endowment effects when initial safe and risky endowments are provided (contribution 1). While Prospect Theory could predict endowment effects in the game, it fails to explain the dominance of interior choices (partial investment). We propose an alternative endowment effect theory that gives predictions that are more consistent with the observed partial investment behavior (contribution 2).
Keywords: C93; D91; H23; 330; Risky investment game; Endowment effects; Loss aversion; Utility curvature; Field experiment; Ethiopia